The Relation between Faith and Reason in Descartes’ Philosophy - Gaidamavičienė, Irena (Problemos, 1971)
The problem of the relationship between faith and reason was vital not only in the l7th century. Its solution gives a methodological basis for the fight against the 20th century dogmatism, especially that of anti-communist theory. On the basis of the achievements of natural sciences Descartes succeeded in proving that theology is incompatible with reason which leads to the conclusion about the ungroundedness of theology (that theology cannot be reasonably grounded). The philosopher’s merit is that he consistently proved the difference between the subject of philosophy and theology. It is shown here that Descartes’ apology to God is only a means – the analysis of this apology revealed the independence of human reason. This meant the victory of thought, science and progress. The inconsistency of Cartesianism and its compromises are but a tribute to the epoch.